A new chronological framework for Chuandong Cave and its implications for the appearance of modern humans in southern China. Issue 178 (May 2023) - Wang, Yanan; Zhang, Xinglong; Sun, Xuefeng; Yi, Shuangwen; Min, Kai; Liu, Dengke; Yan, Wenxuan; Cai, Huiyang; Wang, Xinjin; Curnoe, Darren; Lu, Huayu
Abstract: Chuandong Cave is an important Late Paleolithic site because it documents the early appearance of bone tools in southern China. We used the single-aliquot regenerative-dose protocol for optically stimulated luminescence dating to improve the precision of the chronology for the Chuandong Cave sedimentary sequence. The age of each layer was determined using a Bayesian modeling approach which combined optically stimulated luminescence ages with published AMS 14 C dates. The results showed that Layer 10 began accumulating since 56 ± 14 ka and provides the upper age limit for all artifacts from the sequence. Bone awl tools from Layer 8, the earliest grinding bone tools in this site, were recovered within sediments between 40 ± 7 ka and 30 ± 4 ka. Layer 8 also indicates the appearance of modern humans in the Chuandong Cave sequence. Layers 4–2, ranging from 15 ± 3 ka until 11 ± 1 ka and including the Younger Dryas period, contain a few bone awls and an eyed bone needle. The shift from bone awls to eyed bone needles in the Chuandong Cave sequence indicates that modern humans adapted to the changing climate of southern China. We conclude that modern human behavior in bone tools appeared in southern China as early as 40 ± 7 ka, became more sophisticated during the Last Glacial Maximum, and spread more widely across southern China during the Younger Dryas.